2023
DOI: 10.3390/plants12122369
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Nutrient Cycle in Improved Grain Yield of Dryland Winter Wheat (Triticum aestivum L.) under Hydrological Process of Plant Ecosystem Distribution in the Loess Plateau of China

Hafeez Noor,
Anis Ali Shah,
Pengcheng Ding
et al.

Abstract: Precipitation is the major cause of crop yield variation in rainfed agriculture production in the Loess Plateau. As over fertilization is economically and environmentally undesirable, and crop yield and the resulting returns for N input are uncertain when rainfall variability is high, optimizing N management according to precipitation during fallow season is vital for efficient crop water use and high yield in dryland rainfed farming systems. Results show that the nitrogen treatment rate of 180 treatment signi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…There was changes in external environmental conditions and cultivation measures not only affect the protein content of wheat grains, but also affect the protein composition of wheat grains [ 46 ]. Studies have shown that appropriate increase of nitrogen fertilizer can significantly increase wheat grain protein content [ 15 , 47 ]. The increase of N240, N300 the grain protein content of YH-20410 sowing at maturity stage increased significantly, while the grain protein content.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…There was changes in external environmental conditions and cultivation measures not only affect the protein content of wheat grains, but also affect the protein composition of wheat grains [ 46 ]. Studies have shown that appropriate increase of nitrogen fertilizer can significantly increase wheat grain protein content [ 15 , 47 ]. The increase of N240, N300 the grain protein content of YH-20410 sowing at maturity stage increased significantly, while the grain protein content.…”
Section: Discussionmentioning
confidence: 99%
“…Starch is the most important component in wheat grain, which is mainly composed of amylose and amylopectin. Starch accounts for 60%–70 % of dry grain weight of mature wheat [ 47 , 48 ]. There are few studies on the effect of nitrogen fertilizer on starch content in wheat grains.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Wheat (Triticum aestivum L.) is a major food crop in China, and its cultivation area accounts for approximately 20% of the national arable land in China, which has an important impact on grain production and national economic development [1]. China has the highest fertilizer consumption worldwide, and its fertilizer application accounts for 30.7% of global fertilizer applications [2,3].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we set seven nitrogen application rate gradients. The objectives of this study were (1) to investigate the effects of different nitrogen application rates on group dynamics, the yield, water, and the clear internal relation among each index, and (2) to determine the most suitable nitrogen application range that produced a high yield and high use efficiency in the irrigated district of southern Shanxi Province, based on the net income and environmental benefits.…”
Section: Introductionmentioning
confidence: 99%